Contrasting association of Leptin receptor polymorphisms and haplotypes with polycystic ovary syndrome in Bahraini and Tunisian women: a case–control study. Issue 1 (29th January 2021) - Dallel, Meriem; Douma, Zeineb; Finan, Ramzi R.; Hachani, Feten; Letaifa, Dhafer B.; Mahjoub, Touhami; Almawi, Wassim Y.
Abstract: Background : The present study examined the contribution of ethnicity to the association of leptin receptor gene ( LEPR ) gene variants with polycystic ovary syndrome (PCOS) in Tunisian and Bahraini Arabic-speaking women. Methods : Subjects consisted of 320 women with PCOS, and 446 eumenorrhic women from Tunisia, and 242 women with PCOS and 238 controls from Bahrain. Genotyping of (exonic) rs1137100 and rs1137101 and (intronic) rs2025804 LEPR variants was done by allelic exclusion. Results : The minor allele frequencies (MAFs) of rs1137100 and rs1137101 were significantly different between PCOS cases and control women from Bahrain but not Tunisia, and LEPR rs1137101 was associated with increased PCOS susceptibility only in Bahraini subjects. Furthermore, rs1137100 was associated with decreased PCOS risk among Bahrainis under codominant and recessive models; rs1137100 was negatively associated with PCOS in Tunisians after controlling for testosterone. In addition, rs2025804 was associated with increased PCOS risk among Tunisian but not Bahraini women, after adjusting for key covariates. Negative correlation was seen between rs1137101 and triglycerides in Tunisians, while homeostasis model assessment of insulin resistance (HOMA-IR) and insulin correlated with rs2025804 and rs1137101 among Bahraini subjects, and rs1137101 correlated with estradiol and prolactin. Taking TAG haplotype as common, positive association of TAA and negative association of TGG haplotype with PCOS was seen among Bahraini women; no three-locus PCOS-associated haplotypes were found in Tunisians. Conclusions : The present study is the first to demonstrate the contribution of ethnicity to the association of LEPR gene variants with PCOS, thereby highlighting the significance of controlling for ethnicity in gene association investigations.